RFID-based tollway access and vehicle license plate authentication system - Ting, Adriel C.; Beriong, Danel October B. (2011)
This paper presents a characterization of an automated tollway access and license plate authentication system using RFID technology. Two tags were placed on a vehicle for license plate authentication: one on the windshield and one on the license plate. Simulations of the tag antenna when attached to a license plate were done to observe the effect of metal and implement a proper measure to ensure functionality of the tag. Different spacer materials to be placed between the tag and the plate were simulated and their performances were determined by evaluating the resulting tag antenna's Z1,1 parameters. Prototypes of spacers were tested by measuring the resulting read range of the license plate tag. Field tests were done to determine the maximum speed at which a vehicle should pass through the system for reliable reading of tag data. Speeds from 8 to 20kph were tested for different positions of the windshield tag. A maximum reliable speed of 8kph was achieved, with the windshield tag placed on the upper-middle position on the windshield.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Radio frequency identification systems; Radio frequency -- Identification; Automobile license plates -- Identification; Radio frequency identification (RFID).